Nutrition now - Brown, Judith E. (Belmont, California : Thomson/Wadsworth, 2005)
NUTRITION NOW is your best option to learn about basic nutrition principles and ways you can make the right decisions for meeting your own nutrition needs. The applied, consumer-oriented approach puts you in the driver seat and will show you that there is a lot to learn about the science of nutrition. Additionally, the unique modular format, comprised of 32 individual units, focuses the content into manageable chunks, making it easier to read and retain the material. This edition incorporates up-to-date coverage of the newest research and emerging issues in nutrition. The interactive pedagogical features of this text, along with the author's direct and friendly writing style, make it a favorite among readers. There is also a new "Interactive Learning Guide" available that includes a variety activities that will help you assess and apply your new found knowledge.
Key nutrition concepts and terms -- The inside story about nutrition and health -- Ways of knowing about nutrition -- Understanding food and nutrition labels -- Nutrition, attitudes, and behaviior -- Healthy diets: the dietary guidelines, mypramid, and more -- How the body uses food: digestion and absorption -- Calories: food, energy, and energy balance -- Obesity to underweight: the high and lows of weight status -- Weight control: the myths and realities -- Disordered eating: anorexia nervosa, bulimia, and pica -- Useful facts about sugars, starches, and fiber -- Diabetes now -- Alcohol: the positives and negatives -- Proteins and amino acids -- Vegetarian diets -- Food allergies and intolerances -- Fats and cholesterol in health -- Nutrition and heart disease -- Vitamims and your health -- Phytochemicals and genetically modified food -- Diet and cancer -- Good things to know about minerals -- Dietary supplements and functional foods -- Water is an essential nutrient -- Nutrient-gene interactions in health and disease -- Nutrition and physical fitness for everyone -- Nutrition and physical performance -- Good nutrition for life: pregnancy, breast-feeding, and infancy -- Nutrition for the growing years: childhood through adolescence -- Nutrition and health maintenance for adults of all ages -- The multiple dimensions of food safety -- Aspects of global nutrition -- Appendix A: Table of food composition -- Appendix B: Reliable sources of nutrition information -- Appendix C: The U.S. food exchange system -- Appendix D: Table of intentional food additives -- Appendix E: Cells -- Appendix F: WHO: nutrition recommendations Canada: choice system and guidelines.
Includes bibliographical references.
Keywords: NUTRITION